1986
DOI: 10.1128/iai.53.2.298-304.1986
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in protection provided by immunization against core lipopolysaccharides of Escherichia coli J5 from lethal Haemophilus pleuropneumoniae infections in swine

Abstract: In an investigation of the potential protective effects of immunity against common lipopolysaccharide core antigens of gram-negative bacteria during a severe gram-negative infection in the natural host, we induced Haemophilus pleuropneumoniae infections in weanling pigs immunized with a vaccine of an Rc mutant of Escherichia coli (strain J5). To help define the mechanism involved in J5-mediated protection, we compared the clinical, hematologic, bacteriologic, and serologic responses following an H. pleuropneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

1988
1988
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 20 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Twenty hours later the animals were challenged intratracheally with 5 x 107 CFU of strain J45 (Table 3). Strain J45 was used for challenge studies because this strain is a relatively fresh porcine isolate that has been used in other pathogenesis studies (6). Antiserum to strain K17 was used for passive 0/3 3/3 Monospecific to capsule 80-160 <10 3/3 3/3 Swine antiserum to live 80-160c 40c 2/3 1/3 K17 a Pigs were challenged intratracheally with 5 x 10' CFU of serotype 5 strain J45 20 h after passive transfer of 20 ml of immune or normal swine serum.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty hours later the animals were challenged intratracheally with 5 x 107 CFU of strain J45 (Table 3). Strain J45 was used for challenge studies because this strain is a relatively fresh porcine isolate that has been used in other pathogenesis studies (6). Antiserum to strain K17 was used for passive 0/3 3/3 Monospecific to capsule 80-160 <10 3/3 3/3 Swine antiserum to live 80-160c 40c 2/3 1/3 K17 a Pigs were challenged intratracheally with 5 x 10' CFU of serotype 5 strain J45 20 h after passive transfer of 20 ml of immune or normal swine serum.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 The basis of R mutant immunization is the hypothesis that vaccination with homologous core antigens may provide protection against disease caused by unrelated gram-negative bacteria. Examples of diseases for which heterologous protection using E. coli J5 as a vaccine antigen has been demonstrated include Actinobacillus pleuropneumoniae infections of pigs, 6,7 gram-negative mastitis of dairy cows, [8][9][10] and Edwardsiella ictaluri septicemia in channel catfish. 11 Although Cullor et al 12 demonstrated that calves vaccinated with an experimental bacterin containing E. coli J5 were protected against virulent challenge with Salmonella dublin, field trials with similar vaccines have had mixed results.…”
mentioning
confidence: 99%
“…The capsule may not play a major role in protection, since capsule alone is a poor immunogen (18) and acapsular mutants appear to be as virulent as the parent strain (17). This theory may also be extended to include endotoxin, on the basis of previous work by Fenwick and co-workers (10)(11)(12). However, capsule, endotoxin, and OMPs may be collectively involved in protection.…”
Section: Resultsmentioning
confidence: 99%
“…Capsular polysaccharides are serotype specific and poorly immunogenic (18). Protection with partially purified outer membrane proteins (OMPs) and lipopolysaccharides was comparable with that of current commercial products (10)(11)(12)33), and partial protection was reported for a capsular polymer (17).…”
mentioning
confidence: 84%